2018
DOI: 10.3892/ijmm.2018.3827
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation of human MSCs derived from adipose and amniotic tissues into insulin-producing cells, induced by PEI@Fe3O4 nanoparticles-mediated NRSF and SHH silencing

Abstract: Type 1 diabetes involves the immunologically mediated destruction of insulin‑producing cells (IPCs) in the pancreatic islet. Mesenchymal stem cells (MSCs) have the ability to differentiate into IPCs and have become the most promising means for diabetes therapy. The present study demonstrated that human adipose‑derived stem cells (hADSCs) and human amniotic MSCs (hAMSCs) are able to differentiate into functional IPCs by knocking down neuronal restrictive silencing factor (NRSF) and Sonic hedgehog (SHH). In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It has been reported that hAMSCs possess significant therapeutic effects in multiple disease models, including skin injury, 31 premature ovarian insufficiency, 32 acute liver injury, 33 lung injury, 34 T1 diabetes, 35 chronic kidney disease 36 and so on. MSCs also have shown tremendous potential in anticancer applications because of their innate ability to migrate the tumorigenic sites 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hAMSCs possess significant therapeutic effects in multiple disease models, including skin injury, 31 premature ovarian insufficiency, 32 acute liver injury, 33 lung injury, 34 T1 diabetes, 35 chronic kidney disease 36 and so on. MSCs also have shown tremendous potential in anticancer applications because of their innate ability to migrate the tumorigenic sites 37 .…”
Section: Discussionmentioning
confidence: 99%
“…49,50 After comparing the expression of endogenous Cdc42 protein in ADSCs and rat islets, in accordance with previous studies, we successfully induce ADSCs into IPCs. [51][52][53] Our data indicate that high glucose (4.5 g/L D-glucose) and DMSO (10%) significantly promote the induction of IPCs from ADSCs. Interestingly, after we constructed DTZ staining to further verify the induction of IPCs, some cells in the control group fell off, but the induction group remained.…”
Section: Discussionmentioning
confidence: 99%
“…The reported advantages of hAMSCs include higher cell harvest at the beginning, low donor site morbidity, more "youthful" phenotype, compatibility for use in allogeneic transplants, and powerful immunomodulatory properties compared with hBMSCs and hADSCs (20)(21)(22). Research has proven that hAMSCs protect multiple disease models, including chronic kidney disease (23), T1 diabetes (24), and smoke-induced lung injury (25). However, no study has yet revealed the function of hAMSCs in APAP-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%